NILAI GIZI DONAT YANG DIMODIFIKASI DENGAN JAGUNG DAN BAYAM - Atina Travianita; Zulhaida Lubis; Evawany Yunita Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Food diversification efforts can be done using local food as food diversity. Donuts are usually made using wheat flour is imported foodstuffs, can be modified by making use of local foods such as corn and spinach. Donuts are modified with corn and spinach are also potentially contribute nutrients such as protein, fat, calcium, phosphorus, iron, vitamin A, vitamin B1, and vitamin C. This study aims to determine the acceptability test based on organoleptic properties include color, aroma, flavor, and texture are tested through hedonic test and nutritional content.This study is an experimental research making donuts with the addition of corn and spinach (spinach corn donuts) with different composition ratio of wheat flour, corn, and spinach (5:2,5:2,5, 5:3:2, and 5:2: 3).The results showed that the organoleptic test based on color, aroma, flavor, and texture, spinach corn donuts panelist is the most preferred donuts made with spinach corn 5:2,5:2,5 comparison. Based on the analysis of variance, the addition of corn and spinach with various levels of comparison in the manufacture of corn spinach donut gives a significantly different effect on flavor, aroma, color, and texture of the spinach corn donut generated.The addition of corn and spinach in making donuts increase the content of calcium, phosphorus, iron, vitamin A, vitamin B1, and vitamin C than regular donuts. Advised consumers to make donuts with the addition of corn and spinach as an alternative to reducing food consumption of wheat flour. Diversification also be carried out with the addition of other food as corn and spinach nutrient-rich food.Keywords : Dounut, corn-spinach, nutritive value